(untitled) (Research, Society and Development, 2024)
Meningitis is an infectious disease, characterized by an inflammatory process of the meninges, which are membranes that surround the brain and spinal cord, acting to protect the central nervous system. The objective of the present study was to analyze and recognize the panorama of viral hospitalizations in the state of Pernambuco, as well as diagnosis, treatment and prevention. The study is an epidemiological, cross-sectional, descriptive and quantitative study. The data presented are notifications of viral meningitis in the state of Pernambuco, from January 2013 to December 2022. The state of Pernambuco recorded 4,670 cases of viral meningitis from 2013 to 2022. Of these, 59.6% were from male, with the most affected cities being: Recife (99.2%) and Limoeiro (0.25%). The most affected age group was 01 to 04 years old (25.9%) with 1,210 cases, followed by the 05 to 09 years old group with 1,187 cases and 40-59 years old with 640 cases. Regarding clinical evolution, a higher percentage cure rate was noted (94.66%). In the literature, there is a Brazilian prevalence of meningitis in males, corroborating the study, and in boys up to 9 years of age, viral meningitis was more common. The data presented here is relevant. Even with the existence of immunization offered free of charge by the Unified Health System for the most common etiological agents of meningitis, cases in Pernambuco continue to occur.